Another Step Toward Qualification of Pediatric Physiologically Based Pharmacokinetic Models to Facilitate Inclusivity and Diversity in Pediatric Clinical Studies. Issue 3 (17th November 2022) - Small, Ben G.; Johnson, Trevor N.; Rowland Yeo, Karen
Abstract : Robust prediction of pharmacokinetics (PKs) in pediatric subjects of diverse ages, ethnicities, and morbidities is critical. Qualification of pediatric physiologically‐based pharmacokinetic (P‐PBPK) models is an essential step toward enabling precision dosing of these vulnerable groups. Twenty‐two manuscripts involving P‐PBPK predictions and corresponding observed PK data (e.g., area under the curve and clearance) for 22 small‐molecule compounds metabolized by CYP (3A4, 1A2, and 2C9), UGT (1A9 and 2B7), FMO3, renal, non‐renal, and complex routes were identified; ratios of mean predicted/observed (P/O) PK parameters were calculated. Seventy‐eight of 115 mean predicted PK parameters were within 0.8 to 1.25‐fold of observed data, 98 within 0.67 to 1.5‐fold, 109 within 2‐fold, and only 6 P/O ratios were outside of these bounds. A set of 12 CYP3A4‐metabolized compounds and a set of 6 metabolized by other enzymes, CYP1A2 (1 compound), CYP2C9 (2 compounds), UGT1A9 (1 compound) and UGT2B7 (2 compounds) had 56 of 59 and 22 of 25 mean P/O ratios, respectively, that fell within the > 0.5 and < 2.0‐fold boundaries. For compounds covering renal, non‐renal, complex, and FM03 routes of elimination, 29 of 31 mean P/O ratios fell within the 0.67 to 1.5‐fold bounds, including 4 of 5 P/O ratios from newborns. P‐PBPK modeling and simulation is a strategic component of the complement of precision dosing methods and has a vital role to play in dose adjustment in vulnerable pediatric populations, such as those with disease or in different ethnic groups. Qualification of such models is an essential step toward acceptance of this methodology by regulators.